catena-Poly[trimethylphenylammonium [[bromidocadmate(II)]-mu-bromido-mu-chlorido]] - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title salt, (C9H14N)[CdBr2Cl], the Cd-II atom is five-coordinated in a trigonal-bipyramidal coordination environment. All three of the halogen sites show disorder as a result of substitution of Cl for Br or Br for Cl. Two of the three halogen atoms are involved in bridging a pair of Cd-II atoms, generating a linear polyanionic chain motif.